Strategi Dakwah Penghulu Dalam Membentuk Keluarga Berkualitas Bagi Calon Pengantin - Muhammad Faiz Fadillah; Nurseri Hasnah Nasution (Social Science and Contemporary Issues Journal, 2024)
A da'wah strategy is a plan that contains a series of activities designed to achieve the goals of da'wah so that the da'wah runs well and smoothly. For the Penghulu's Da'wah Strategy in forming a quality family at the Kemuning District Religious Affairs Office, the Penghulu has implemented various methods including da'wah strategies in order to form a healthy and quality family. The family is the smallest unit in society which has an important role in forming quality individuals. In this context, the headman as a religious figure has a significant role in guiding the prospective bride and groom in forming a quality family based on religious teachings. The aim of this research is to analyze the penghulu's preaching strategy in forming a quality family for the prospective bride and groom. This research uses a qualitative approach by conducting a literature review and content analysis related to the penghulu's da'wah strategy. The results of the analysis show that there are several strategies that can be used by the bride and groom to form a quality family for the bride and groom. Data analysis techniques consist of data reduction, data presentation, and drawing conclusions. Based on research results, according to Poerwadarmita, coaching is an effort, action and activity that is carried out efficiently and successfully to obtain better results. A personal approach is an important strategy that allows the celebrant to interact individually with the bride and groom. By understanding the background, needs and personality of the bride and groom, the celebrant can convey the da'wah message in a relevant and easy-to- understand manner. The celebrant needs to provide solid religious education to the prospective bride and groom, including an understanding of Islamic teachings and the application of religious values in everyday life. This will equip the prospective bride and groom with a strong foundation in building a family based on religious values.